FLUID ANALYSIS OF MAGNETIZED PLASMA SHEATH IN A CYLINDRICAL GEOMETRY - Thakur, P. K.; Pokhrel, R. R.; Khanal, R. (Journal of Institute of Science and Technology, 2018)
Plasma sheath formed in front of a material wall plays an important role in overall plasma properties. Magnetized plasma sheath for both collisional and collisionless cases in a cylindrical co-ordinate system was studied using a fluid model. The fluid equations were compiled for the considered geometry and were solved numerically, using the fourth-order Runge-Kutta method for prescribed boundary and initial conditions. The ion velocity along the axis of the cylinder and the ion density profiles were studied for collisionless and collisional cases and at different obliqueness of the magnetic field. The ion velocities acquired its maximum value at the wall with monotonic increment in collisionless cases, whereas the ion density profile was not monotonic in collisionless case as well as when the obliqueness of the magnetic field starts increasing. In such cases, the ion density increases close to the entrance and then decreases monotonically towards the wall. The study provides insight to plasma properties in cylindrical plasmas which are common in discharge tubes, light sources and plasma jets.